PENDIDIKAN KARAKTER DALAM MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP 3 PEKALONGAN: (Kajian atas Kurikulum dan Proses Pembelajaran) - Maemonah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2011)
Even though character building as an autonomous subject among student does not exist in secondary school, Islamic Education (PAI), as one of the subjects in school related to character building, has to play its role in building studentsí character. This study aims to reveal the problems related to PAI learning process in SMP 3 and its role in building studentsí noble character. This study was qualitative using observational case studies. The data were obtained through interviews, questionnaires, and documents and were analyzed using qualitative analysis techniques with the inductive approach. The documents were such legal decisions of officials in Educational Ministry, the syllabi, curriculums, and teaching planning (RPP). The result shows that PAI learning has an important role in building studentsí noble character if it is supported by competent lecturers, good inputs, adequate materials, and good processes. Character building learning was taught integrated and aimed to shape noble character among the students of SMP 3 Pekalongan. It was accommodated in PAI learning, citizenship learning and local contain subject, such as Javanese language and Cookery Learning. Unfortunately, the sustainability and comprehensiveness of character building learning in PAI curriculum were not seriously attended. Nevertheless, they were taught integrated in pilot project program and evaluated gradually and comprehensively.